Application of PCM in Glass Facade of High-rise Apartment for Thermal Performance Improvement - Litani Evitasari; Ima Defiana; FX Teddy Badai Samodra (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
In high-rise building systems, the envelope, one of which is the facade, has a major role in the reception of heat into the building. This type of glass facade material has properties that can transmit solar heat directly, so that the heat that enters the building is trapped inside and makes the temperature in the room increase. Therefore, there is a need for a solution or solution to reduce the temperature in the room. Currently, technology is increasingly developing, so there are many variations of materials that effectively reduce the cooling load of the space. One of them is PCM (Phase Change Material) which can be used to store the heat energy that enters through the building envelope in very large quantities. To find out the effect of PCM material on the glass facade in the apartment, a study was carried out. The purpose of this study was to evaluate and analyze the effect of the application of PCM material on the facade of the apartment on the temperature in the room. The method used in this study is an experimental method, using field measurements and simulations with Design Builder software. The results of the simulation with PCM material obtained that the most optimal material configuration for thermal reduction is a combination of double glass (tinted and reflective) with PCM gap (Bio-PCM), the temperature reduction is 1.84oC. The effect of thermal performance inside the building on orientation at 60% WWR with double glass and gap Bio-PCM, namely east orientation is better at reducing heat around 2-8oC. compared to the west, north and south orientations.